PENGARUH POLITIK DAN AGAMA DALAM PERKEMBANGAN KAJIAN HADIS DI YAMAN PADA ABAD KE-7 HINGGA KE-10 MASEHI - Tri Marsela, Ratih; Putri Salsabillah, Rosa; Muhid, Muhid (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
This article discusses the political and religious influences on the development of hadith studies in Yemen during the 7th-10th centuries CE. Yemen, as one of the centers of Islamic scholarship, played an important role in the transmission and teaching of hadith. This study explores how political conditions such as changes in power and the influence of schools of thought influenced the methodology of hadith studies in Yemen. The different approaches between the Sunni and Zaydi schools are also examined as factors that enrich, as well as challenge, efforts to standardize hadith methodology in the region. Using a historical and social approach, the study highlights the dynamic relationship between political power and the development of hadith scholarship as well as how educational institutions played a role in propagating different understandings. The results show that the development of hadith in Yemen was not only influenced by theological aspects but also by complex social and political dynamics.